PERANAN FINANCIAL TEKNOLOGI DIGITAL MENGGUNAKAN MARKET PLACE SERTA ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN DAMPAKNYA PADA LOYALITAS KONSUMEN (Studi Empiris Pengguna Marketplace UMKM Kota Tangerang Selatan) - Kartolo, Rachmat; Sugiyanto, Sugiyanto; Supratikta, Hadi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The role of financial technology is considered to be at the forefront of digital market developers through market places to increase the income of MSMEs in South Tangerang City. The objectives of this research are 1.) To test and analyze whether financial technology influences purchasing decisions 2). analyzing Online Customer Reviews on purchasing decisions 3). testing financial technology and Online Customer Reviews simultaneously influence purchasing decisions 4). To test and analyze whether purchasing decisions have an impact on consumer loyalty in South Tangerang City MSMEs. The method used in this research is a quantitative method. Primary data collection was carried out by distributing questionnaires to MSMEs using the market place. Population of all business actors in South Tangerang City. The sample uses questionnaires and interviews. The sampling technique used is a random sampling technique. The analysis tool in this research is SEM (Structural Equation Modeling) processed through the AMOS (Analysis of Moment Structure) program. The research results can be concluded as follows: (1). There is a partial effect of financial technology on purchasing decisions using a value of 52.5% obtained from the determinant test. (2) Online Customer Reviews influence purchasing decisions (3). financial technology and Online Customer Reviews simultaneously influence purchasing decisions (4). Purchasing Decisions that impact Consumer Loyalty.